2013
DOI: 10.1109/tcbb.2012.147
|View full text |Cite
|
Sign up to set email alerts
|

The Depth Problem: Identifying the Most Representative Units in a Data Group

Abstract: This paper presents a solution to the problem of how to identify the units in groups or clusters that have the greatest degree of centrality and best characterize each group. This problem frequently arises in the classification of data such as types of tumor, gene expression profiles or general biomedical data. It is particularly important in the common context that many units do not properly belong to any cluster. Furthermore, in gene expression data classification, good identification of the most central uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
8
0
2
Order By: Relevance
“…Group T formed by 107 samples from tumors on liver cancer patients, group NT formed by 76 samples from nontumor tissues of liver cancer patients and group N formed by 30 samples from normal livers. In [42] it was shown that there exists a high degree of confusion between groups, so bad one-class classification results are expected. Taking groups N, NT, and T as target classes, the typicality approach obtained AUC average values and standard deviation values 86.04 ± 3.95, 80.86 ± 3.07, and 55.62 ± 3.76, respectively.…”
Section: Results Of the Experimental Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Group T formed by 107 samples from tumors on liver cancer patients, group NT formed by 76 samples from nontumor tissues of liver cancer patients and group N formed by 30 samples from normal livers. In [42] it was shown that there exists a high degree of confusion between groups, so bad one-class classification results are expected. Taking groups N, NT, and T as target classes, the typicality approach obtained AUC average values and standard deviation values 86.04 ± 3.95, 80.86 ± 3.07, and 55.62 ± 3.76, respectively.…”
Section: Results Of the Experimental Studymentioning
confidence: 99%
“…Given the real-valued coordinates Z = Ψ( Y ), it is possible to apply any standard multivariate technique. Such an approach was used by different authors [3542]. In this context a general measure of dispersion of Y , the geometric variability V δ of C , with respect to δ can be defined by Vδ(C)=12false∫S×Sδ2(boldyi,boldyj)f(boldyi)f(boldyj)λ(dboldyi)λ(dboldyj) which is a variant of Rao's diversity coefficient [43].…”
Section: One-class Classificationmentioning
confidence: 99%
“…Era asko daude Z zorizko p-bektoreak adierazten duen C populazioarekiko z aleak duen sakonera neurtzeko. Bereziki, distantzietan oinarrituriko sakonera [22] honela definitzen da:…”
Section: Sakoneraunclassified
“…Sakonera erlatiboa delako kontzeptua [22] ere definitu da. C r , r = 1, …, k klaseak harturik, C r klaseari dagokion alearen sakonera erlatiboa, klase horrekiko dagokion sakoneraren eta gainontzeko klaseekiko duen sakonera handienaren arteko diferentzia da.…”
Section: Sakoneraunclassified
“…There are many possibilities how to define the depth of the data (Liu, 1990;Vardi and Zhang, 2000;Zuo and Serfling, 2000;Serfling, 2002), nevertheless the computation of the most popular depth functions is very slow, in particular, for high-dimensional data the time needed for classification grows rapidly. A new less-computer intensive depth function I (Irigoien et al, 2013a) was developed, but the authors did not study its use in relation to the classification problem.…”
Section: Introductionmentioning
confidence: 99%